Cognitive functions and disability progression in relapsing-remitting multiple sclerosis: A longitudinal study. Issue 2 (4th March 2021) - Heled, Eyal; Aloni, Roy; Achiron, Anat
Abstract: Longitudinal studies have shown inconsistent findings regarding the association between cognition, demographic characteristics, and clinical decline in relapsing-remitting multiple sclerosis (RRMS). Our objective was to further explore these relations, over time, while also considering age and sex. A total of 183 patients with RRMS were assessed at two time points, using a neuropsychological battery and the Expanded Disability Status Scale (EDSS). For the first assessment, participants were divided by age (<29, 30–39, 40–49, 50–60) and sex. Next, they were divided according to their participation in one of three interval assessment points: 2–3, 4–5, and 6–8 years. Cognitive function was not correlated with disease duration but was negatively correlated with EDSS score. Men under 29 and women under 39 showed negative correlations between cognitive and clinical impairment. Executive functions, attention, and information processing speed (IPS) showed cognitive decline between the first and second assessments. Furthermore, at the 4–5 year interval IPS predicted EDSS scores, while at the 6–8 year interval it was IPS and visuo-spatial ability. Therefore, relation between clinical status and cognition is not consistent across different age and sex groups. Additionally, cognitive deterioration is only partially evident longitudinally; however, IPS appears to be the most sensitive in predicting one's future clinical condition.